The effect of technology supported teaching on students' academic achievement: a combined meta-analytic and thematic study. (2018) - Batdi, Veli; Aslan, Aydin; Zhu, Chang
This research aimed to enlighten the ambiguous relationship between technology supported teaching (TST) and students' achievement. A meta-analysis was conducted incorporating the quantitative findings of 11 scientific studies derived from 245 theses and 386 articles. These addressed the effect of technology on students' academic achievement nationally and internationally between 2005 and 2016. The results indicate that TST has a positive effect on students' academic achievement. Furthermore, participants' perceptions of this issue were thematically derived from 12 academic studies and these corroborated the quantitative findings. Learners should therefore be exposed to innovative technologies such as Web 2.0 and augmented reality technologies to effectively and adequately benefit from them as learning strategies. The results of both studies are discussed in detail and suggestions made for future research.